Comparison of Substance‐Based and Whole‐Effluent Toxicity of Produced Water Discharges from Norwegian Offshore Oil and Gas Installations. (28th July 2022) - de Vries, Pepijn; Jak, Robbert G.; Frost, Tone K.
Abstract: When assessing the environmental risks of offshore produced water discharges, it is key to properly assess the toxicity of this complex mixture. Toxicity can be assessed either through the application of whole‐effluent toxicity (WET) testing or based on its substance‐based chemical composition or both. In the present study, the toxicity assessed based on WET and substance‐based was compared for 25 offshore produced water effluents collected for the Norwegian implementation of the Oslo–Paris convention risk‐based assessment program. The objectives were, firstly, to examine the concurrence between toxicity estimates derived from these two lines of evidence; and, secondly, to evaluate whether toxicity of produced water discharges predicted from substance‐based data is adequately addressed in comparison with ground truth reflected by WET. For both approaches, 50% hazardous concentrations (HC50s) were calculated. For at least 80% of the effluents the HC50s for the two approaches differed by less than a factor of 5. Differences found between the two approaches can be attributed to the uncertainty in the estimation of the concentration of production chemicals that strongly influences the substance‐based estimated toxicity. By evaluating effluents on a case‐by‐case basis, additional causes were hypothesized. Risk management will particularly benefit from the strength of risk endpoints from both approaches by monitoring them periodically in conjunction over time. This way (in)consistencies in trends of both indicators can be evaluated and addressed. Environ Toxicol Chem 2022;41:2285–2304. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.